Assessing the Program Satisfaction of Pioneering Graduates of the Bachelor in Secondary Education–Science: Evidence from a Philippine State University - Rey-Mark G. Basagre (Language, Literature and Education: Research Updates Vol. 5, 2025)
Introduction: The Bachelor in Secondary Education (BSE) major in Science is a four-year program that has a good number of chemistry and physics courses to enable the graduates to teach physical sciences courses. After the implementation of the new teacher education curricular program, the BSE major in Science program had its first batch of graduates in the academic year 2021-2022. Yet, studies on the implementation of this new curricular offering have not yet been carried out. Purpose of the Study: This study aimed to determine the program Satisfaction of the Pioneering Graduates of the BSE major in Science. Methodology: This study utilised a descriptive survey as a method of research. This study uses a Likert scale to assess the BSEd-Science program graduates’ satisfaction with the curriculum and instruction, facilities, and student support. This study involved 24 BSE Science graduates from State University in the Bicol Region, Philippines, for the academic year 2021-2022. Data were treated using mean, frequency, and rank. Interviews with college administrators, graduates, and the employers of the graduates were also conducted to gather relevant data that could help in the analysis of results. Results: Results showed that the graduates are “satisfied” with the program’s curriculum and instruction, support to students, and facilities, with a mean of 4.4, 4.37, and 4.01, respectively. The strengths and areas for improvement of the program were identified. The identified strengths of the program are an organised and flexible curriculum, learner-centred and academic freedom, relevant competencies, approachable and competent faculty, and good resources and facilities. The data revealed that the program helps students to develop knowledge and skills, offers a holistic approach, offers hands-on activities that build students’ competence to teach different disciplines of Science, and helps with the growth and development of the learners in a learner-centred environment. The identified themes for the areas for improvement of the program are the improvement of the laboratory room and apparatus, hands-on laboratory activities, and others. Conclusion: Overall, the students are “satisfied” with implementing the new program. Since the program has an organised and flexible curriculum and offers relevant competencies, further improvement of the laboratory room and laboratory apparatus, including hands-on laboratory/culminating activities, must be conducted to enhance the program’s effectiveness further.